![\(\begin{matrix} y=ln(x+3)\\ e^y=x+3\\ e^y-3=x\\ swap ~x~and~y\\ \huge\underline{y=e^x-3}} \end{matrix}\) ](https://tex.z-dn.net/?f=%5C%28%5Cbegin%7Bmatrix%7D%0Ay%3Dln%28x%2B3%29%5C%5C%0Ae%5Ey%3Dx%2B3%5C%5C%0Ae%5Ey-3%3Dx%5C%5C%0Aswap%20~x~and~y%5C%5C%0A%20%5Chuge%5Cunderline%7By%3De%5Ex-3%7D%7D%0A%20%5Cend%7Bmatrix%7D%5C%29%0A)
To get the inverse
of any function f(x) [ just make sure that it passes the horizontal line test]
follow the steps:
- Solve for x, i.e separate x in one side
and the other terms in the other side, included f(x).
- Swap x and f(x).
- The result is the inverse of the original
function
.
-------------------------
Apply that on your function
Answer:
.
Step-by-step explanation:
From the given graph it is clear that the y-intercept is 16.
The line passes through (-2,24) and (2,8). So, slope of line is
Slope intercept form of a line is
where, m is slope and b is y-intercept.
Substitute m=-4 and b=16 in the above equation.
Therefore, the required equation is
.
1). y-3=-2(x+4)
2) slope = 3/4
y+2=3/4(x+4)
y=3/4x +1
3x-4y=4
looks like only the last one
Answer:
the answer would be 4
Step-by-step explanation:
10 - 4 = 6 divided by 1.25 = 4
hope this helps!